Knowledge Games : How Playing Games Can Solve Problems, Create Insight, and Make Change - Schrier, Karen (Karen L.) (Book collections on Project MUSE., 2016)
Imagine if new knowledge and insights came not just from research centers, think tanks, and universities but also from games, of all things. Video games have been viewed as causing social problems, but what if they actually helped solve them? This question drives Karen Schrier's Knowledge Games, which seeks to uncover the potentials and pitfalls of using games to make discoveries, solve real-world problems, and better understand our world. For example, so-called knowledge games?such as Foldit, a protein folding puzzle game, SchoolLife, which crowdsources bullying interventions, and Reverse the Odds, in which mobile game players analyze breast cancer data?are already being used by researchers to gain scientific, psychological, and humanistic insights. Schrier argues that knowledge games are potentially powerful because of their ability to motivate a crowd of problem solvers within a dynamic system while also tapping into the innovative data processing and computational abilities of games. In the near future, Schrier asserts, knowledge games may be created to understand and predict voting behavior, climate concerns, historical perspectives, online harassment, susceptibility to depression, or optimal advertising strategies, among other things. In addition to investigating the intersection of games, problem solving, and crowdsourcing, Schrier examines what happens when knowledge emerges from games and game players rather than scientists, professionals, and researchers. This accessible book also critiques the limits and implications of games and considers how they may redefine what it means to produce knowledge, to play, to educate, and to be a citizen.